Study on the efficacy, safety, and biomarkers of nusinersen in type II and III spinal muscular atrophy in children - Chen, Liyuan; Liu, Fen; Fang, Danna; Li, Jianwei (Frontiers in Pediatrics, 2023)
The time span for the approval of nusinersen to treat SMA remains short. Most studies on the efficacy and safety of this drug within clinical trials, are lacking real-world research data. This study is based on real-world studies of SMA patients in children with type II and III SMA and is committed to objectively evaluating the effectiveness and safety of this drug.A retrospective analysis was conducted on the clinical data of 18 children with type II and III SMA from January 2022 to June 2023. The motor function assessment scale, SMN protein, platelet, liver and kidney function, and other laboratory indicators of all patients before and after treatment were collected for statistical analysis.After load dose treatment( after 64 days of treatment), compared with baseline, the Revised Upper Limb Module (RULM) of SMA patients showed significant improvement(improvement rate：44%), confirming the short-term effectiveness of the drug. The increase in cerebrospinal fluid SMN protein was greater in patients with significant improvement in motor function than in patients without improvement in motor function. Compared with baseline, there was no significant increase in AST and ALT levels in SMA patients, indicating that the drug had almost no effect on the liver.After each treatment, thrombocytopenia and partial urinary protein positivity may occur, but it could recover before the next treatment. This indicates that nusinersen is 字体: (默认) Times New Roman, (中文) 宋体, 小四, 非加粗, 无下划线, 图案: 清除(自动设置) 设置格式[作者]:potentially harmful to platelet and renal function, although the effect is weak and reversible.Nusinersen has shown good efficacy and overall safety, but platelets and urinary protein are still indicators that require long-term monitoring. the increase in cerebrospinal fluid SMN protein was greater in patients with significant improvement in motor function than in patients without improvement in motor function.